The Location and Effects of Visual Hemisphere-Specific Stimulation on Reading Fluency in Children With the Characteristics of Dyslexia. (July 2018) - Koen, Bobbie Jean; Hawkins, Jacqueline; Zhu, Xi; Jansen, Ben; Fan, Weihua; Johnson, Sharon
Fluency is used as an indicator of reading proficiency. Many students with reading disabilities are unable to benefit from typical interventions. This study is designed to replicate Lorusso, Facoetti, Paganoni, Pezzani, and Molteni's (2006) work using FlashWord, a computer program that tachistoscopically presents words in the right or left visual hemi-field in English and locates through fMRI imaging the processing areas involved in fluency development. Our participants were 15 students who were ages 8 to 19 years and had reading disabilities randomly assigned to Intervention ( n = 9) and Delayed Intervention ( n = 6) groups. Functional imaging studies focused on analyzing activations in the left hemisphere (LH) superior temporal gyrus, the inferior frontal gyrus, and the LH inferior occipito-temporal/fusiform area (visual-word form area [VWFA]). Analysis of intervention data showed that 6 of the 9 Intervention group participants (67%) achieved levels of automatic processing and increased their reading rate by an average of 20 words per minute after participating in the FlashWord intervention. Analyses of fMRI group activation maps and mean activation levels in regions of interest document processing changes in VWFA activations that could be related to the increase in reading speed and confirm these locations as essential to developing fluency.